Multiple Myeloma and Bisphosphonate-Related Osteonecrosis of the Mandible Associated with Dental Implants - Luis Junquera; Lorena Gallego; Alejandro Pelaz (Hindawi Limited, 2011)
Multiple myeloma (MM) is a malignant plasma cell disorder and more than 30% of patients with this pathology develop osteolytic lesions in the jaw. Either pamidronate or zoledronic acid is recommended in patients with MM who have one or more lytic lesions. However, bisphosphonate-related osteonecrosis of the jaws (BRONJ) has been described as a complication associated with their use. Otherwise, the use of endosseous implants in oral rehabilitation is a well-established procedure, with good long-term success although systemic factors may affect the bone healing around dental implants. We report the first case reported of MM adjacent to a mandibular dental implant in a patient who developed BRONJ in the same area after intravenous zoledronate treatment. We discuss possible pathogeny of this particular and interesting phenomena.